PENYEBAB DAN PENCEGAHAN KORUPSI: KASUS INDONESIA - Subhan Sofhian (Tatar Pasundan: Jurnal Diklat Keagamaan, 2020)
After 75 years of Indonesian Independence, the country is supposedly be developed and prosperous, as well as categorized to Super-power state, since it has abundant resources and potential demographic. However, the conditions that occur today cannot be progressed from the state of developing country. What makes Indonesia's not-so-good including massive and systematic corruption? Based on the premise, researchers review the documentation, rules, and regulations related to corruption issues. Are there enough rules? Or is there another cause that makes these rules blunt and helpless against reality? Based on the results of analyzing the rules and phenomena over government institutions, researchers conclude that the main factor of corruption in Indonesia occurs for human factors, especially those who own good strengths in government, economic, and social aspects.Key words: corruption; power; regulation; economy